Menerapkan Prinsip 2 Timotius 1:7 dalam Pelayanan Penginjilan - Prabowo, Wisnu (Sekolah Tinggi Teologi IKAT Jakarta, 2019)
As God's creation, humans are given spirits by God; the spirit has various functions and uses in life. In 2 Timothy 1: 7 it is written about the spirit of fear, a spirit that awakens strength, love and order. This article examines the meaning of